Architectonics of Musics. Esperienze multidisciplinari alla Columbia University (L'architettura delle città - The Journal of the Scientific Society Ludovico Quaroni, 2019)
Music, like architecture, is an immersive experience – it surrounds you. One can turn away from a painting or a work of sculpture, while music and architecture engulf the body in space. “Architectonics of Music” records the series of Studios taught at Columbia University on music and architecture. They are part of a larger project to develop cross-disciplinary, inspiration-provoking work on new architectural languages. Steven Holl began this studio in 2006 and continued the masterclasses in several editions at Columbia University up to 2018. The design experimentations began with a full immersion investigation translating a music excerpt into space, material and form. Teams of students analyzed works of 20th century composers with an eye to the geometric potential of translation into architecture and consequently focused on transcribing the concept into architectural models. The results from the 2013 edition are presented in the framework of the whole experience of the seven editions of the advanced studio workshop as well as in the context of Steven Holl’s research on Architecture and Music.